(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The article reveals the potential of the socio-cultural space of a traditional folk holiday in the aspect of the formation of value orientations of the younger generation. The urgency of the problem is due to the increased attention to the search for effective ways to form the value orientations of adolescents in modern society, in the system in which the traditional folk holiday culture occupies a special place. A comparative and theoretical analysis of the literature on the research issue is utilized to meet the study’s aim. The paper analyzed the state of practical activities of cultural and leisure institutions with adolescents and concluded that the study of the traditional folk holiday as a socio-cultural space for the formation of the personality of adolescents allows justifying its great educational potential in the value-forming process.